2016
DOI: 10.1038/srep38351
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific Association Between Uric Acid and Outcomes After Acute Ischemic Stroke: A Prospective Study from CATIS Trial

Abstract: The relationship between serum uric acid (UA) and outcomes after acute ischemic stroke remains debatable in human studies, and the sex effect on this association has yet to be explored. Here, we investigated these associations in a prospective study from the China Antihypertensive Trial in Acute Ischemic Stroke. Baseline UA levels were measured in 3284 acute ischemic stroke patients. Primary outcome was defined as a combination of death and major disability (modified Rankin Scale score ≥3) at 3 months. UA leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
3
12
1
1
Order By: Relevance
“…The population had a marked female predominance, which is consistent with several previous studies. 3,[17][18][19] In addition, the average age close to 40 years old also agrees with the different epidemiological reports worldwide, where it is estimated that the pathology has higher prevalence in patients between 25 and 55 years of age. 1,3,[20][21][22] Regarding the diagnoses, the proportion of migraine without aura (37%) was similar to a previous study in the Colombian population (43%).…”
Section: Discussionsupporting
confidence: 88%
“…The population had a marked female predominance, which is consistent with several previous studies. 3,[17][18][19] In addition, the average age close to 40 years old also agrees with the different epidemiological reports worldwide, where it is estimated that the pathology has higher prevalence in patients between 25 and 55 years of age. 1,3,[20][21][22] Regarding the diagnoses, the proportion of migraine without aura (37%) was similar to a previous study in the Colombian population (43%).…”
Section: Discussionsupporting
confidence: 88%
“…A meta-analysis indicated that the serum uric acid level had a protective effect on neurological outcomes after acute ischemic stroke [22]. Further study showed elevated serum uric acid was positively associated with a better prognosis in men, but not in women [23]. In the present study, we did not find an association between the degree of artery stenosis and uric acid.…”
Section: Discussioncontrasting
confidence: 71%
“…Despite the fact that hyperuricemia often occurs in SLE patients, the association between LN and hyperuricemia remains insufficiently studied. Furthermore, serum uric acid levels have been reported to have variable effects on chronic heart failure [15], cardiac hypertrophy in CKD patients [16], acute ischemic stroke [17] and IgAN [18], depending on sex; nevertheless, its sex-specific effect on LN remains unclear. In an analysis of the Korean National Health Insurance system, the prevalence of SLE in Korea was reported to be 18.8-21.7 per 100,000 people in 2006 and has been increasing since [19].…”
Section: Introductionmentioning
confidence: 99%